Level of Activity Daily Living in Post Stroke Patients - Whitiana, Greesea Dinamaria; Vitriana, Vitriana; Cahyani, Aih (Althea Medical Journal, 2017)
Background: Stroke is the leading cause of disability and dependency which directly decrease patientâslife quality . Disability caused by stroke can be prevented by holistic and comprehensive management plan of stroke. Until now, there was no study conducted to evaluate management for post stroke patients in Dr. Hasan Sadikin General Hospital (RSHS). Therefore, this studyaimed to describe level of activities of daily living (ADL) in post stroke patients in Neurology unit of RSHS as a basic evaluation for a better management hereafter.Methods: This descriptive quantitative study participated by 31 post-stroke outpatients in Neurology Policlinic of RSHS was conducted from September to October 2015. Interviews were done to assess level of ADL by the Barthel Index score. VariablesÂ  correlated with ADL (age, gender, stroke type, stroke occurrence, stroke risk factors and muscle strength) were collected from medical records. Collected data was input and presented in tables. Results: There were 19 females and 12 males with the age group of 55-64 year old (35.5%). Most subjects had first stroke attack (71.0%). The most common type and risk factor were ischemic stroke (83.9%) and hypertension (81%) respectively. Patients with a maximum score in the entire extremity muscle strength were in the range of 60-70%. Out of the 31 patients, 18 (58.1%) were classified as independent in ADL. Conclusions: The majority of post stroke patients in the Neurology unit of RSHS wereindependent in ADL. Â DOI:Â 10.15850/amj.v4n2.1068